Advances in energy systems for valorization of aqueous byproducts generated from hydrothermal processing of biomass and systems thinking. Issue 10 (15th April 2019) - Gu, Yexuan; Zhang, Xuesong; Deal, Brian; Han, Lujia; Zheng, Jilu; Ben, Haoxi
Abstract : Advances in energy systems for the valorization of the aqueous byproduct generated from the hydrothermal processing of biomass: a perspective and review of the recent progress. Abstract : Hydrothermal processing ( e.g., hydrothermal liquefaction) is one of the most promising systems to valorize a wide range of biomass. However, a large amount of aqueous byproduct is generated, which contains high soluble concentrations of both organics and nutrients. Thus, valorization of the aqueous byproduct can be clearly beneficial for the environment and energy recovery. Various physicochemical systems have been recognized for the valorization of aqueous byproducts, such as chemical, thermochemical, and electrochemical systems. Accordingly, this article reviews the valorization of the aqueous byproduct from hydrothermal processing (mainly hydrothermal liquefaction) from several points of view, starting with the characteristics of the aqueous byproduct originating from the hydrothermal processing of diverse biomass. The recent progress in numerous physicochemical systems, including catalytic hydrothermal gasification and microbial electrolysis cells, is comprehensively demonstrated with emphasis on their combinations since integrated systems allow energy and nutrients to be recovered more environmentally and economically feasible. The fundamentals, advantages, limitations, and the most recent findings faced in the development of each physicochemical system are also elucidated. Subsequently, the new concept of systems thinking is proposed to evaluate these systems, and a systemic framework is presented to consolidate the practical applications of these systems. Consequently, this review illustrates both the future perspectives of wastewater valorization and the milestones that should be achieved in the future.